Comparative Analysis of Various Testing Techniques used for Aspect-Oriented Software System - Sandeep Dalal; Susheela Hooda (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Nowadays, Aspect-Oriented Programming (AOP) paradigm is getting more popularity in the field of software development. But testing an Aspect-oriented software system (AOSS) is not well matured. Therefore, many researchers have been focusing on testing an AOSS. Moreover, the literature indicates that very few papers have devoted to literature survey but still there is need to study in depth of various testing techniques used for AOSS. Therefore, in this paper, a comprehensive study of existing various testing techniques for AOSS have been conducted and present a comparative analysis result of various testing techniques based on various parameters.